PEMBERIAN SEDUHAN JAHE TERHADAP FREKUENSI MUAL MUNTAH PADA IBU HAMIL TRIMESTER 1 DENGAN EMESIS GRAVIDARUM DI PMB KECAMATAN SENDURO KABUPATEN LUMAJANG - Sulima, Sulima; Sulistiyah, Sulistiyah; Retnaningsih, Reny (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Nausea, vomiting that occurs during pregnancy is caused by increased levels of the hormones estrogen and progesterone produced by Human Chorionic Gonadotropin in the serum from the placenta. This study aims to determine the effect of giving ginger infusion on the frequency of nausea and vomiting in 1st trimester pregnant women with emesis gravidarum in PMB Senduro District, Lumajang Regency in 2024. This research used a quasi-experimental design with a pre-posttest control group design. The population of all pregnant women in the first trimester with emesis gravidarum in the PMB Senduro District, Lumajang Regency in the period January-April 2024 was 40 pregnant women. The sampling technique using a purposive sampling, analyzed using Mann-Whitney test. The frequency of nausea and vomiting tn the intervention group, before giving the ginger brew was an average of 9.4 times per day and after giving the ginger infusion the frequency of nausea and vomiting was an average of 5.6 times. In the control group who were not given ginger infusion, the frequency of nausea and vomiting was 9.2 times per day beforehand and 8.5 times afterward. The results of Mann Whitney test showed a p-value of 0.001 < α (0.05), which means that there was an effect of giving ginger infusion on the frequency of nausea and vomiting in first trimester pregnant women with emesis gravidarum in PMB Senduro District, Lumajang Regency